Noise Mapping with Surfer Software as Noise Depiction in Water Treatment Plant PT. Z - Ridha Farhan; Anita Camelia; Irine Yulianingsih (Postgraduate, University of Mataram, 2025)
PT Z operates in the production of clean water, which has the potential to generate noise due to machinery used in the processing process or clean water dosing system. Noise that occurs in the production area can affect the health and comfort of operators and visitors who are in the location. This study aims to identify noise levels, recommended exposure duration, areas exposed to noise, as well as analyze the causes of noise and provide proposals for its control. The noise measurement method used refers to the noise mapping method and uses a sound level meter. The data obtained was then processed into contour maps with purple, green, yellow, orange, and red color variations using Surfer 16 software. The results showed that the highest noise level reached 86.5 dB, while the lowest was 56.7 dB. Based on calculations using the NIOSH formula from 40 measurement points in the noise mapping method, there are 7 points that require increased noise control. The highest noise level was recorded at 86.5 dB with an exposure duration of 5.65 hours (393 minutes). Noise control efforts can involve three elements, noise sources, noise dispersal paths, and noise receivers, which are matched with the control hierarchy referenced from the Permenaker No. 5/2018.